E-023 Intravenous oxygen carrier therapy delays infarct size progression in a canine large vessel occlusion model. (4th August 2020) - King, R; Shazeeb, M; Kolstad, J; Raskett, C; Winger, J; Kelly, L; Vardar, Z; Kraitem, A; Anagnostakou, V; Krtolica, A; Henninger, N; Gounis, M
Abstract : Introduction: Neuroprotective strategies represent a significant opportunity to delay infarct progression in patients suffering a Large Vessel Occlusion (LVO), allowing more time for treatment by mechanical thrombectomy. Oxygen carrier therapy has the potential to deliver oxygen to hypoxic tissues, allowing for a longer window of treatment before cell death. Methods: Twenty-three dogs were used in this study, with an additional 14 historical controls. Autologous clot was injected into the left MCA, confirmed on DSA, and the dog was transferred to a 3T MRI. In order to determine infarct evolution rate, Perfusion Weighted Imaging was performed and relative Time to Peak (rTTP) maps were generated. 1 Based on the initial infarct evolution pathway (slow or rapid progressors), animals were randomized to either receive oxygen carrier or vehicle control. Regardless of evolution pathway, or treatment group, IV bolus was given 45 minutes after clot placement. Following bolus, diffusion weighted imaging (DWI) was performed every 30 minutes to assess infarct evolution. After 5 hours, dogs were removed from the MR, euthanized and the brain was explanted for histological processing. To calculate the true infarct volume, apparent diffusion coefficient (ADC) was calculated from the DWI images, and a threshold value of 0.533 × 10 -3 mm 2 /s was used to differentiate infarct. The predicted final infarct size was taken from rTTP maps as the area with greater than 4.5s delay and used to normalize infarct volume. Results: Of the 23 dogs used in the active group, 5 were excluded due to spontaneous recanalization or lack of sufficient infarct on DWI. From the included 18 dogs, 11 were identified as rapid progressors, and 7 as slow. The figure shows the average infarct growth rate for the four groups, showing the oxygen carrier increasing the time needed for the infarct to reach 50% of its expected size by approximately 45 minutes in the rapid group, and 30 minutes in the slow. Overall the final infarct size was reduced in both the rapid and slow groups, 0.99 vs 0.87 control versus treatment, and 0.97 vs 0.92 control versus treatment, respectively (p<0.001 and 0.022). Conclusions: Oxygen carrier therapy shows promise to slow down the infarct growth after an LVO, allowing for more time to perform mechanical thrombectomy. Not only was the time to 50% infarct increased, but after 5 hours, the infarct in the oxygen carrier groups still showed an area of penumbra. Reference: Transl Stroke Res . 2019 Sep 3. Disclosures: R. King: None. M. Shazeeb: None. J. Kolstad: None. C. Raskett: None. J. Winger: 5; C; Omniox Inc. L. Kelly: 5; C; Omniox Inc. Z. Vardar: None. A. Kraitem: None. V. Anagnostakou: None. A. Krtolica: 5; C; Omniox Inc. N. Henninger: 1; C; K08NS091499. M. Gounis: None.